Bases moleculares de la sordera: envejecimiento y nuevas fronteras en la investigación auditiva - Cervantes, Blanca; López Larrubia, Pilar; Varela-Nieto, Isabel; Murillo-Cuesta, Silvia (Auditio, 2025)
Age-related hearing loss, or presbycusis, is one of the most prevalent causes of sensory impairment in the world. This condition, which is multifactorial in nature, is influenced by genetic, environmental, physiological and lifestyle factors. In recent years, its relationship with cognitive impairment and neurodegenerative diseases has aroused great interest among researchers and health professionals. In this contribution, the molecular mechanisms involved in age-related auditory degeneration are reviewed, with special emphasis on the role of oxidative stress, neuroinflammation, as well as genetic mutations that are associated with increased susceptibility to presbycusis, both in animal models and in epidemiological and clinical trials. It also discusses diagnostic imaging techniques and emerging therapeutic perspectives that could transform the clinical approach to deafness in the near future.